2021
DOI: 10.1128/msystems.00988-21
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderiaceae and Multidrug Resistance Genes Are Key Players in Resistome Development in a Germfree Soil Model

Abstract: This is the first study to examine how resistomes develop and evolve using GS. GS can be used to study the colonization and establishment of bacterial communities under antibiotic selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Multiple Drug Resistance ARGs (MDR) dominated the dataset in number (n = 87) and relative abundance, particularly in surface bio lms (79%, 87% and 83% of the reads per million in wood, W-LDPE and LDPE, respectively, vs 36% in water). MDR is known to dominate ARGs in soil microcosms (Cao et al, 2021) as well as in miningimpacted soil samples (Yi et al, 2022), or even in ready-to-eat food (Li et al, 2020). The reported levels of MDR in the literature are in line with our ndings, where MDR accounts for a high proportion of the number of reads and the highest number of genes associated with AMR (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Multiple Drug Resistance ARGs (MDR) dominated the dataset in number (n = 87) and relative abundance, particularly in surface bio lms (79%, 87% and 83% of the reads per million in wood, W-LDPE and LDPE, respectively, vs 36% in water). MDR is known to dominate ARGs in soil microcosms (Cao et al, 2021) as well as in miningimpacted soil samples (Yi et al, 2022), or even in ready-to-eat food (Li et al, 2020). The reported levels of MDR in the literature are in line with our ndings, where MDR accounts for a high proportion of the number of reads and the highest number of genes associated with AMR (Fig.…”
Section: Resultssupporting
confidence: 88%
“…In this context, some of the bacterial taxa found in the plastisphere in the present study have been found to carry ARGs, such as the Burkholderiaceae family, which is a primary carrier of ARGs in situations of high antibiotic concentrations (Cao et al, 2021), such as those occurring in site 2. The genus Acinetobacter, which is part of the core microbiome detected in the PET bottle after 6 months of colonization in site 2, is responsible for the persistence of macrolide resistance ARGs in WWTP effluents, which would also explain the higher relative abundance of ermF in this sites and colonization phase (April et al, 2022).…”
Section: Discussionmentioning
confidence: 68%
“…Multiple Drug Resistance (MDR) genes dominated the dataset in number ( n = 84) and relative abundance, particularly in surface biofilms (61%, 77% and 66% of the RPKM in wood, W-LDPE and LDPE, respectively , vs. 27% in water). MDR is known to dominate ARGs in soil microcosms [ 31 ] as well as in mining-impacted soil samples [ 158 ], or even in ready-to-eat food [ 79 ]. The reported levels of MDR in the literature are in line with our findings, where MDR accounts for a high proportion of the number of reads and the highest number of genes associated with AMR [ 28 , 134 , 154 ] (Fig.…”
Section: Resultsmentioning
confidence: 99%